Evaluation of harvest yield and beverage quality of coffee under ethylene application - Martynelly Nogueira Gois, Caroline; Ferreira, Sindynara; Gois, José Laurício; Ribeiro Malta, Marcelo (Revista Agrogeoambiental, 2023)
The coffee plant is characterized by the irregular ripening of its fruits. This uneven ripening often makes it impossible to optimize its harvest, since green fruits are more adhered to the plant than those in the ripe and overripe stages. In addition, it can influence the final product’s beverage quality. The use of ethylene is an alternative to optimize and increase the harvest yield of coffee, besides reducing expenditures on labor and post-harvest ground picking. This study was carried out to examine the harvest yield of coffee variety Mundo Novo IAC 379/19 under different ethylene rates as well as to analyze beverage quality in the different treatments. The experiment was laid out in a randomized-block design with four treatments (ethylene rates: 0, 300, 500, or 700 mL ha-1). The plots consisted of nine plants and three replications, but only the three central plants were evaluated. Results were analyzed by Tukey’s test at a significance level of 5%. The rates of 700 and 300 mL ha-1 provided the lowest amount of green fruits, whereas the percentage of ripe fruits was equivalent between treatments. The treatment with 700 mL ha-1 resulted in the highest percentage of fruits in the overripe stage, among the evaluated rates. Ethylene use did not increase harvest efficiency. Control treatment provided a significantly higher number of green fruits. Additionally, the use of ethylene-induced changes in the chemical composition of the bean and beverage quality.